2020
DOI: 10.1186/s43161-020-00016-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of respiratory therapy on pulmonary functions in children with cerebral palsy: a systematic review

Abstract: Background Children with cerebral palsy (CP) are at risk for respiratory dysfunction. Early initiation of pulmonary rehabilitation in addition to conventional physical therapy may result in improvement and maintenance of chest mobility and respiratory function. However, empirical support for respiratory therapy is limited. The aim of the review was to assess the evidence of the effectiveness of respiratory therapy on pulmonary functions in children with CP. Methods Four electronic databases (PubMed, Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In general, the studies have a great variation in relation to the number of sessions and session time. We observed that the optimal level of intensity in intervention programs for CP is not clear [13].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In general, the studies have a great variation in relation to the number of sessions and session time. We observed that the optimal level of intensity in intervention programs for CP is not clear [13].…”
Section: Discussionmentioning
confidence: 81%
“…Pulmonary rehabilitation in children with chronic lung diseases has been extensively studied and points out protocols with respiratory exercises aimed at chest mobility and abdominal muscle strengthening, which lead to improved chest expansion and increased lower thoracic mobility, thus suggesting better diaphragmatic work and increased quality of life and exercise capacity [7][8][9][10][11]. Some of these exercises were also proposed for children with CP [12,13]. However, available rehabilitation strategies to target the respiratory functioning of the population with CP are not addressed in the literature; protocols are not standardized, and there is no consensus on the optimal training modalities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curvature, rotation, and shortening of the spine result in thoracic cage deformity 9,62 . A deformed thoracic cage causes reduced lung volume, decreased lung compliance, increased stiffness of the chest wall, reduced force of the respiratory muscles, and increased mechanical dysfunction of the diaphragm.…”
Section: Physical Examination Essential and Specific Aspects And Additional Testsmentioning
confidence: 99%